Perilaku Anak Single Parent Menurut Analisa Pendidikan Agama Islam - Faradila Nuriyah (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
Education is an educator's effort to guide and direct his students according to their physical and spiritual development, so that they excel in all fields and face all life's problems fairly according to the applicable rules. According to Islamic teachings, a family begins with two people who are brought together and asked to choose partner. The most important task of the family is to create a generation that grows up and has noble character, is useful and participates as a member of society and helps in all things. Islamic education can generally be understood as an effort to increase faith, understanding, appreciation and practice of the Islamic religion in order to become Muslims. who have faith and faith and have noble morals in personal, social, national and state life. The aim of this research is to reveal the influence of Islamic religious education on the attitudes of children with single parents, the sub-focus of which is: 1) Implementation of Islamic religious education. 2) The attitude of single parents. 3) The influence of Islamic religious education on the attitudes of children from single parent families.